Monitoring and market power in loan markets - Ari Hyytinen; Otto Toivanen (Bank of Finland, 2000)
Whether or not banks are engaged in ex ante monitoring of customers may have important consequences for the whole economy.We approach this question via a model in which banks can invest in either information acquisition or market power (product differentiation). The two alternatives generate different predictions, which are tested using panel data on Finnish local banks.We find evidence that banks' investments in branch networks and human capital (personnel) contribute to information acquisition but not to market power.We also find that managing customers' money transactions enhances banks ability to control their lending risks.
URN:NBN:fi:bof-20140807478
Keywords: 330